2021
DOI: 10.1037/bne0000427
|View full text |Cite
|
Sign up to set email alerts
|

NMDA lesions in the prefrontal cortex delay the onset of maternal, but not infanticidal behavior in pup-naïve adult mice (C57BL/6).

Abstract: While most pup-naïve adult female mice can display, or be induced (by repeated exposure to pups) to display parental behavior rapidly, adult males are infanticidal or nonparental. The medial prefrontal cortex (mPFC) participates in attentional selection, decision-making, behavioral flexibility, and planning that may be critical in the rapid display of parental or infanticidal behavior. We investigated if NMDA-induced lesions in the mPFC (targeting prelimbic cortex) inhibited maternal or infanticidal behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…They suggested that dams with mPFC lesions might show deficits in integrating motor and sensory information and filtering out irrelevant stimuli, consistent with the general role of the mPFC in executive function. More recently, Alsina-Llanes and Olazábal (2021) investigated whether cell-specific mPFC lesions (targeting prelimbic cortex) delayed the onset of maternal behavior in pup-naïve adult female mice (C57BL/6). All control females displayed full maternal behavior at the first encounter with pups, while only 50% of lesioned females did.…”
Section: Basic Functions Of the Mpfc And Its Roles In Maternal Behaviormentioning
confidence: 99%
“…They suggested that dams with mPFC lesions might show deficits in integrating motor and sensory information and filtering out irrelevant stimuli, consistent with the general role of the mPFC in executive function. More recently, Alsina-Llanes and Olazábal (2021) investigated whether cell-specific mPFC lesions (targeting prelimbic cortex) delayed the onset of maternal behavior in pup-naïve adult female mice (C57BL/6). All control females displayed full maternal behavior at the first encounter with pups, while only 50% of lesioned females did.…”
Section: Basic Functions Of the Mpfc And Its Roles In Maternal Behaviormentioning
confidence: 99%
“…A study on virgin male and female mice found that the mPFC lesion (targeting the prelimbic cortex) significantly affected number of females and males showing pup cares and infanticide. 50% females in lesioned group exhibited maternal while 100% of sham operated groups show maternal care, whereas the 100% lesioned males exhibited infanticide, 83% of control males showed infanticide (Alsina-Llanes & Olazábal, 2021). It has been reported that the mPFC is highly activated in human mothers when they hear cry from their babies (Lorberbaum et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The mPFC is involved in attention switching, decision-making, behavioral flexibility and planning, making it potentially crucial for rapidly expressing pup care or infanticide behavior (Alsina-Llanes & Olazábal, 2021). It has been reported that the mPFC is highly activated in human mothers when they hear cry from their babies (Lorberbaum et al, 2002).…”
Section: Introductionmentioning
confidence: 99%